Reflective learning style and academic burnout in students of the Master’s Degree of Teaching and Health Research - Palomino Rocha, Katia Yovanna (2020)
Objective. To determine the relationship between learning styles and burnout syndrome in students of the Master’s Degree of Teaching and Health Research at UNMSM, 2018. Methods. It was descriptive, correlational, prospective, cross-sectional. A simple random probability sampling was carried out, resulting in a sample of 95 students to whom a survey was applied through a questionnaire. Results. The learning style of the students from highest to lowest appearance. Reflective (55.8%), pragmatic (21.1%), active (15.8%) and theoretical (7.4%). The majority of the prevalence of academic burnout syndrome was “mild” (58.9%), followed by “moderate” (28%) and “no burnout” (12.6%). Conclusion. There is no relationship between the learning styles and the academic burnout syndrome of students. The predominant learning style being reflective and presenting mild academic burnout